The rational use of glucocorticoids may reduce the risk of readmission in menopausal women with knee osteoarthritis: results from a five-year longitudinal study - Huang Xi; Hao Huiqin; Liu Hongqi; Zhang Ruqi; Zhang Junfeng (Arthritis Research & Therapy)
Abstract Objective To investigate the effect of glucocorticoids (GCs) on the risk of readmission in menopausal women with knee osteoarthritis (OA). Information and methods The study cohort comprised 80 menopausal women with knee OA treated at a tertiary hospital affiliated with Shanxi Medical University and who underwent follow-up between September 2018 and September 2023. Then the collected longitudinal monitoring data were used to construct a semi-variable coefficient shared Gamma frailty model (VCSGF). Based on the results of this model, we explored the impact of GCs on menopausal women with knee OA and made risk predictions. Results The mean patient age at study entry was 64.7 ± 9.3 (range 50–82 years). And during the research, patients were admitted to the hospital a mean of 2.4 ± 1.8 times (range 1–11 times). Compared to patients who have not used the drug, the risk of early readmission in patients who have used GCs was reduced by 96% (HR = 0.04, 95%CI: 0.006 ~ 0.284, $$\:P<0.001$$ ). This protective effect diminished over time ( $$\:{γ\:}_{2l}\left({t}_{0}\right)=0.629,P<0.001$$ ). In addition, the risk of hospital admission with recurrent symptoms was roughly 3.35-fold higher in patients who drink alcohol than in patients who do not (95%CI: 1.661~6.794, $$\:P<0.001$$ ). Conclusion GC use reduced the risk of readmission in menopausal women with knee OA, although this effect diminished over time. Therefore, in patients without further contraindications, GCs may be used in moderation to reduce the readmission risk. In clinical practice, additional research is needed to investigate the timing and appropriate use of GC in the treatment of menopausal women with knee OA, and to develop a more rational program for GC use.